Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Dan Dampaknya Terhadap Loyalitas Pelanggan Apotek Di Kecamatan Serang - Syifauddin, Muhammad Rizal; Hatta, Iha Haryani; Sarnianto, Prih (JRB-Jurnal Riset Bisnis, 2023)
Pharmacies continue to grow and make business competition between pharmacies increase and reduce drug prescriptions, that require pharmacies to optimize marketing mix strategies that are useful in building customer loyalty. The main purpose of this study is to determine the influence of marketing mix variables on purchasing decisions and its impact on customer loyalty of Apotek in serang district. In this quantitative study, primary data was collected through interviews using a structured questionnaire that has been validated. The data of the research was collected using a random sample of 200 respondents of Pharmacy customers from 3 pharmacies in Serang District. Data analysis using the Structural Equation Modeling software AMOS 23. The results showed that products that are varied, complete and always available have an influence on purchasing decisions and customer loyalty. Low prices have an influence on purchasing decisions and customer loyalty. Location has no effect on purchasing decisions or customer loyalty because Serang District is a densely populated area and the proximity of pharmacies makes location selection not a customer's consideration. Promotion has no effect on purchasing decisions or customer loyalty because promotional activities are carried out only through word of mouth, pharmacies should preferably carry out digital promotions through advertising or television media. People influence purchasing decisions and customer loyalty because pharmacists can explain drugs in detail and behave friendly. The process influences purchasing decisions but does not affect customer loyalty because customers prefer the service process to be fast and easy. Physical evidence has no effect on purchasing decisions or customer loyalty because complete facilities are not a major consideration and the goal is to buy drugs. And the purchasing decisions positive and significant impact on customer loyalty.